X‐ray‐induced acoustic computed tomography for 3D breast imaging: A simulation study - Tang, Shanshan; Yang, Kai; Chen, Yong; Xiang, Liangzhong (Medical physics (Lancaster), 2018)
Purpose The objective of this study is to demonstrate the feasibility of x‐ray‐induced acoustic computed tomography (XACT) for early breast un‐palpable microcalcification (μCa) detection in three dimensions (3D). The proposed technique provides the true 3D imaging for breast volume which overcomes the disadvantage of the tissue superposition in mammography. Methods A 3D breast digital phantom was rendered from two‐dimensional (2D) breast CT slices. Three different tissue types, including the skin, adipose tissue, and glandular tissue, were labeled in the 3D breast phantom. μCas were manually embedded in different locations inside the breast phantom. For each tissue type, the initial pressure rise caused by the x‐ray‐induced acoustic (XA) effect was calculated according to its themoacoustic properties. The XA wave's propagation from the point of generation and its detection by ultrasound detector array were simulated by Matlab K‐Wave toolbox. The 3D breast XACT volume with μCa was acquired without tissue superposition, and the system was characterized by μCas placed at different locations. Results The simulation results illustrated that the proposed breast XACT system has the ability to show the μCa cluster in 3D without any tissue superposition. Meanwhile, μCa as small as 100 μm in size can be detected with high imaging contrast, high signal to noise ratio (SNR), and high contrast to noise ratio (CNR). The dose required by the proposed XACT configuration was calculated to be 0.4 mGy for a 4.5 cm‐thick compressed breast. This is one‐tenth of the dose level of a typical two‐view mammography for a breast with the same compression thickness. Conclusions The initial exploration for the feasibility of 3D breast XACT has been conducted in this study. The system feasibility and characterization were illustrated through a 3D breast phantom and simulation works. The 3D breast XACT with the proposed system configuration has great potential to be applied as a low‐dose screening and diagnostic technique for early un‐palpable lesion in the breast.